2019
DOI: 10.1002/tafs.10138
|View full text |Cite
|
Sign up to set email alerts
|

Differential Marking of Embryos by Location and Date of Release Reveals Within‐River Natal Homing and Parental Influence on Progeny Return Timing in Sockeye Salmon

Abstract: The tendencies of salmon and trout to spawn in proximity to their natal sites and follow the parental timing of breeding are fundamental to their population structure and also affect the performance of enhancement facilities. Specifically, an understanding of how parental spawning date and offspring release location affect the timing and place of breeding by returning adults is important for the evaluation of hatchery supplementation programs and their integration with sympatric naturally spawning populations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Assortative mating based on phenotype has been studied in a number of wild fish species, with the majority of examples around the world focused on the evolution of traits such as size (de Borghezan et al, 2019 ; Rios Moura et al, 2021 ; Rueger et al, 2016 ) or color (Utagawa et al, 2016 ). In the North Pacific Ocean, long‐term ecological monitoring studies on salmon (e.g., Barnett et al, 2019 ; Ford et al, 2015 ; Lin et al, 2017 ; May, 2022 ; Peterson et al, 2014 ) have found many cases of spatial and temporal assortative mating. This assortative mating based on temporal (May, 2022 ) or spatial (Lin et al, 2017 ; Peterson et al, 2014 ) variation in spawning behavior suggests that assortative mating in space and time can have positive effects on fitness and population productivity (May, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Assortative mating based on phenotype has been studied in a number of wild fish species, with the majority of examples around the world focused on the evolution of traits such as size (de Borghezan et al, 2019 ; Rios Moura et al, 2021 ; Rueger et al, 2016 ) or color (Utagawa et al, 2016 ). In the North Pacific Ocean, long‐term ecological monitoring studies on salmon (e.g., Barnett et al, 2019 ; Ford et al, 2015 ; Lin et al, 2017 ; May, 2022 ; Peterson et al, 2014 ) have found many cases of spatial and temporal assortative mating. This assortative mating based on temporal (May, 2022 ) or spatial (Lin et al, 2017 ; Peterson et al, 2014 ) variation in spawning behavior suggests that assortative mating in space and time can have positive effects on fitness and population productivity (May, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…During their adult life stages, they migrate long distances back to their natal stream, relying on odor memories to return to the natal site for spawning, years after they left it as juveniles. Thus, the olfactory system must be sufficiently developed at early juvenile stages to acquire chemosensory information needed for learning (imprinting to) natal stream odors that are used later to guide homing migrations (Barnett et al, 2019 ; Brannon, 1972 ; Quinn et al, 2006 ; Zielinski & Hara, 1988 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, sockeye salmon, O . nerka , disperse from their natal streams into nursery lakes, where they rear, typically for 1 or 2 years, before the PST and migration to the sea, yet successfully home to the natal tributaries or even specific parts of those tributaries (Barnett et al, 2019; Quinn et al, 2006) rather than the lake outlet they experienced as smolts. Furthermore, juvenile coho, Chinook ( O .…”
Section: Introductionmentioning
confidence: 99%